Instytucjonalizacja i wzory uprawiania socjologii w Polsce na tle światowej nauki = Institutionalization and patterns of practicing sociology in Poland - Kraśko, Nina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper is concerned with the development and institutionalization of Polish sociology viewed against that of the world. The autor`s thesis is that since the 2nd Republic of Poland it is the American pattern of practicing sociology (both in terms of its kontent and methods) that has been dominating. As for the organisation of science, however, it has been in Poland very much like in other European countries. It is not until the last two decades that these organisational patterns have tended to be more and more American all over Europe as well.
Keywords: socjologia; Polska